Single nucleotide polymorphisms of USP26 in azoospermic men. (1st November 2016) - Luddi, Alice; Crifasi, Laura; Quagliarello, Antonella; Governini, Laura; De Leo, Vincenzo; Piomboni, Paola
ABSTRACT: Some studies have focused on the association between male infertility and single nucleotide polymorphisms (SNPs) in the ubiquitin-specific protease 26 ( USP26) gene, but the results are controversial. In this case-control study including both normozoospermic men and patients with nonobstructive azoospermia, we analyzed both the entire coding region and 5' and 3' untranslated regions of USP26 in order to identify genetic variants in this gene to investigate the role of USP26 on spermatogenesis. We reported variations in the USP26 gene sequence in 82% of azoospermic and in 50% normospermic men. The synonymous variation c.576G>A has a frequency significantly different in the azoospermic (60.2%) and normozoospermic (23.6%) groups, while the frequencies in the two groups of both c.1090C>T and c.1737G>A missense mutations did not reach statistical significance. A cluster mutation (c.371insACA, c.494T>C) was detected in 2 normozoospermic men (2.7%). In the 5'UTR we identified the -33C>T variation both in azoospermic (3.8%) and in normozoospermic (2.7%) men. In a normozoospermic man we detected the nonsense mutation c.882C>A, never reported to date. According to our results, we suggest that only the variation c.576G>A has a frequency significantly different in azoospermic compared to normozoospermic men. Moreover, the identification in a normozoospermic man of a nonsense mutation (c.882C>A) which causes the production of a truncated protein, suggests a marginal role of USP26 in male spermatogenesis. Additional studies may be useful as we cannot exclude that the other SNPs may represent risk factors for male fertility acting by an oligogenic/polygenic mechanism.